PENGARUH WARNA BENIH TERHADAP PERTUMBUHAN DAN PRODUKSI SAWI (Brassica juncea L) - Abdullah Sarijan (AGRICOLA, 2011)
Experimental planting of mustard (Brassica juncea L) asing seed color as the treatment, carried out on clay soil in the village Asano, Abepura district in June to August 2006. The results showed that the color of the seed treatment was statistically not give different results on observations of plant heigltt, Ieaf number, flowering, Ieaf number a harvest, fresh weight and & dry weight of plant cultivation; but based on observation data seen a tendency to produce brown seeds growth and better production